Innovációs rendszerek a közép-európai nem nagyvárosi térségekben: A Dél-dunántúli régió példája - Páger, Balázs (Közép-Európai Közlemények, 2013)
The role of the knowledge0based development has increased in the regional economic development at the beginning of 21st century and there are similar initiations in the development of Central and Eastern European regions. The cooperation of the actors with knowledge potential is one of the some key factors to the knowledge0based development. The role of regional innovation systems in the emerging of innovation and in the regional development process is argued by many Hungarian and international studies. I review in this paper shortly the main elements of the theory of regional innovation system, I show some characteristics of the Central and Eastern European nonmetropolitan regional innovation systems and I present the case of South Transdanubian region as a case study of these CEE regions. The innovation system of the South Transdanubian can be a good example how difficult to create a suitable regional innovation system in an economic monocentric country, although the most important elements of the system are available in the region. The other aim of the examination of the South0Transdanubian regional innovation system is the presentation of the vulnerable points of the system.